Demographic forecasts, migration and transition theory: a labor market perspective - BRUNI, Michele (Papeles de Población; Vol. 15 Núm. 62 (2009), 2009)
The paper proposes a new logical system to build demographic scenarios based on a model that explain migration inflows as a function of the manpower needs that countries with below replacement fertility are experiencing, as a result both of the decline in Working Age Population and employment growth.  Using this approach we show that the WAP of countries characterized by low fertility will necessarily increase; that the migration balance of numerous countries will turn from negative to positive well before 2050; that the level of the international migration flows will progressively increase to unprecedented values so that at least 250-300 million people will move from developing countries to developed countries in the next 50 years; that the decline in fertility and the relative rates of employment growth of developed and developing countries will determine radical changes in the pattern of international migrations. The last part of the paper discusses some policy implications of this vision of the future.